BALDONE OBSERVATORY IN THE CIRCLES OF TIME - Eglitis, I. (Одеські астрономічні публікації, 2019)
1957 – The first laboratory building, known as the White House, was built near Baldone on the Riekstu hill, in the territory of the next Observatory. 01.01.1958 – The Astronomy Sector was separated from the Institute of Physics and commenced independent activi- ty as the Laboratory of Astrophysics at the Latvian Acade- my of Sciences (LAS). In 1967, with the decision of the Presidium of the Latvian SSR LAS the Laboratory of As- trophysics was transformed into the Radioastrophysic Ob- servatory at LAS. Under the leadership of the first director, Janis Ikaunieks, an instrumental observation base develops – a 1.2m Schmidt telescope was installed in 1966 for opti- cal observations. The project of the variable base radio in- terferometer after the death of J. Ikaunieks was unrealized. To continue astronomical observations in radio range, in 1972 10m radio telescope RT-10 was purchased. Non-stationary processes and spectral research of car- bon stars are associated with the study in optic range de- velops following the plan of J.Ikaunieks. After the estab- lishment of the UL Institute of Astronomy in 1997, the field of research in the optical range is supplemented by the research direction of small objects of the solar system. However, the area of radio astronomy has stopped due to lack of funding. The scientific potential of the Baldone Observatory re- mains significant. It should be mentioned that the 22,000 Schmidt telescope astroplate archive obtained in 1967- 2005, will be digitized entirely this year. After digital im- age processing, coordinates and brightness for about of 330,000,000 objects will be obtained. The database will contain details of star movement, brightness variability (both long-term and short-term) and details of known, unknown asteroids and comets. In 2008, monitoring of asteroids in the Solar System is started in Observatory. Up till now 77 new asteroids have been discovered in the Solar System and 11 of them have been named. Research on carbon stars is still continuing successfully. The number of carbon stars currently discovered has reached 400. A methodology has been created for estimat- ing the temperature and distance to the carbon stars. Work is currently underway to improve this method. Observatory is continuing its work on popularizing as- tronomy. Number of visitors per year has risen from 1000 in 90s to almost four thousand in 2018.